Pregnancy in a woman with Kallmann-De Morsier syndrome: A case report - Ibtissam Bellajdel; Fatima-Zahra Mounassib; Hafsa Taheri; Chaymae Rochdi; Hanane Saadi; Mohammed Choukri; Ahmed Mimouni (Clinical and Experimental Reproductive Medicine, 2026)
Kallmann syndrome is characterized by the combination of hypogonadotropic hypogonadism and anosmia. It is a clinically and genetically heterogeneous disorder. We report the case of ovarian stimulation in a woman with Kallmann-De Morsier syndrome, resulting in a pregnancy achieved through insemination, which progressed to term. The patient underwent cesarean section for a contracted pelvis and delivered a live female infant. Drawing upon a review of the literature on Kallmann-De Morsier syndrome, we discuss the role of follicle-stimulating hormone during the follicular phase, as well as criteria for monitoring ovarian stimulation.